Signal and information processing, networking and computers : proceedings of the 1st International Congress on Signal and Information Processing, Networking and Computers (ICSINC 2015), Beijing, China, October 17-18, 2015 /: proceedings of the 1st International Congress on Signal and Information Processing, Networking and Computers (ICSINC 2015), Beijing, China, October 17-18, 2015. ([2016]) - Unknown
No abstract available